Amiloride inhibits mammalian renal kallikrein and a kallikrein-like enzyme from toad bladder and skin. - Margolius, H S (1980)
Renal kallikrein is localized in luminal plasma membranes of the mammalian distal nephron and gains access to urine from this site. Its activity is regulated, in part, by aldosterone. These facts led us to study the effects of amiloride, a drug known to inhibit sodium reabsorption and potassium secretion at this site, on kallikrein activity. Amiloride inhibited the esterolytic activity of purified rat or human urinary kallikrein or of rat renal cortical cells upon a synthetic substrate (ID50 = 0.12-0.23 mM). Kinetic analyses showed that the enzyme inhibition was noncompetitive and reversible in nature. The kinin-generating activity of kallikrein acting upon kininogen substrates was also inhibited by amiloride, as measured by bioassay in the rat uterus of guinea pig ileum or by radioimmunoassay of liberated kinins (ID50 = 85 microM). No other diuretic drug tested inhibited kallikrein activity, except triamterene, which did so, weakly. In addition, kallikrein-like enzyme activity was discovered in the urinary bladder or skin of Bufo marinus toads and this activity was also inhibited by amiloride. The localization of the enzyme and its inhibition by this drug suggest that further study of relationships amongst the glandular kallikrein-kinen system and renal ion and water transport is warranted.